Deterministic Capture of Individual Circulating Tumor Cells Using a Flow-Restricted Microfluidic Trap Array - Yousang Yoon; Jusin Lee; Ki-Chun Yoo; Onejae Sul; Su-Jae Lee; Seung-Beck Lee (Micromachines, 2018)
Circulating tumor cells (CTCs) are regarded as a strong biomarker which includes clinically valuable information. However, CTCs are very rare and require precise separation and detection for effective clinical applications. Furthermore, downstream analysis has become necessary to identify the distinct sub-population of CTCs that causes metastasis. Here, we report a flow-restricted microfluidic trap array capable of deterministic single-cell capture of CTCs. The extent of flow restriction, correlating with the device geometry, was then optimized using a highly invasive breast cancer cell line (LM2 MDA-MB-231) to achieve 97% capture efficiency with a single-cell capture rate of 99%. Single-cell capture of CTCs from mice with full-blown metastasis was also demonstrated. The single-CTC capturing ability of the flow-restricted trap array not only showed cell enumerating ability but also high prospects for application in future automated downstream analysis.